2014
DOI: 10.11144/javeriana.upsy13-2.pepm
|View full text |Cite
|
Sign up to set email alerts
|

Predictores del estrés parental en madres de familias en riesgo psicosocial

Abstract: r e s u m e N En este estudio se han analizado las relaciones entre el estrés parental, las competencias parentales percibidas y la contribución de factores sociodemográficos y psicológicos para la explicación del estrés parental. Participaron 80 madres portuguesas usuarias de servicios de protección a menores en riesgo. Los resultados mostraron niveles muy elevados de estrés parental -especialmente en madres con hijos adolescentes y desempleadas-y relaciones significativas entre el estrés y las competencias p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
6
0
4
Order By: Relevance
“…Studies analyzing social factors that could be determinant in parenting, have found that parental stress is more prevalent in families in a vulnerable situation (Ceballo and McLoyd, 2002;Chaudry and Wimer, 2016). Factors commonly associated with this vulnerability are low parent education (Raikes and Thompson, 2005), single parenting (Olhaberry and Farkas, 2012), economic problems, unemployment and low-qualification jobs (Duncan and Brooks-Gunn, 2000;Ayala-Nunes et al, 2014). These also seem to be facilitators not only of parental stress, but of low self-perception of competence as parents (Raikes and Thompson, 2005;Morrison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Studies analyzing social factors that could be determinant in parenting, have found that parental stress is more prevalent in families in a vulnerable situation (Ceballo and McLoyd, 2002;Chaudry and Wimer, 2016). Factors commonly associated with this vulnerability are low parent education (Raikes and Thompson, 2005), single parenting (Olhaberry and Farkas, 2012), economic problems, unemployment and low-qualification jobs (Duncan and Brooks-Gunn, 2000;Ayala-Nunes et al, 2014). These also seem to be facilitators not only of parental stress, but of low self-perception of competence as parents (Raikes and Thompson, 2005;Morrison et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Parenting sense of competence is one of the most relevant dimensions to be assessed in order to grasp the dynamics and processes that occur within the family system. Parenting sense of competence has been associated with several important parental outcomes such as parental behavior and actual competence (Coleman & Karraker, 1997;Shumow & Lomax, 2002), parental depression (Cutrona & Troutman, 1986;Gondoli & Silverberg, 1997;Teti & Candelaria, 2012) and parenting stress (Ayala- Nunes, Lemos & Nunes, 2014;Begle & Dumas, 2011;Bloomfield & Kendall, 2012;Scheel & Rieckmann, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Aunque no se encontró diferencia entre los niveles de depresión postparto y estado civil de las madres, se encontró que el grado de instrucción se relaciona negativamente con la depresión postparto. Esto podría sugerir, como se ha reportado en diversos estudios (4,10,12,21), que el nivel socioeconómico es un factor determinante en la ocurrencia de la depresión postparto, ya que el grado de instrucción se encuentra fuertemente asociado al nivel socioeconómico.…”
Section: Discussionunclassified